1995
DOI: 10.1002/clc.4960181305
|View full text |Cite
|
Sign up to set email alerts
|

Receptor systems involved in norepinephrine release in heart failure: Focus on dopaminergic systems

Abstract: The sympathetic nervous system is under extraordinarily complex modulation, involving numerous presynaptic and postsynaptic control mechanisms. These highly conserved and very redundant control mechanisms allow for the sympathetic nervous system to adapt quickly and precisely to altered environmental stress or conditions. Heart failure (HF) is characterized by excessive sympathetic activity, with both enhanced “spillover” and reduced clearance of norepinephrine (NE). The normal inhibitor control mechanisms app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Sympathetic nerve system (SNS) regulates the function of innervated effector organs through releasing and terminating neurotransmitter NE (Esler et al, 1990;Francis, 1995). The released transmitters in the cleft bind receptors on the postsynsptic membrane through diffusion, transmitting the signals to the postsynaptic neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sympathetic nerve system (SNS) regulates the function of innervated effector organs through releasing and terminating neurotransmitter NE (Esler et al, 1990;Francis, 1995). The released transmitters in the cleft bind receptors on the postsynsptic membrane through diffusion, transmitting the signals to the postsynaptic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The norepinephrine transporter (NET) at presynaptic nerve terminals mediates the uptake of released norepinephrine (NE), resulting in the rapid termination of synaptic transmission and thereby controlling the fine tuning of neuronal activities (Esler et al, 1990;Povlock and Amara, 1997). Age-related reduction in reuptake of NE and β-AR density in the heart of health senescent human and animals was reported (Esler et al, 1990;1995;Chevalier et al, 1991;Dawson and Meldrum, 1992;Sakai et al, 1992;White et al, 1994;Ferrara et al, * Project supported by the Postdoctoral Fellow Foundation of the Science and Technology Committee of Shanghai and the Natural Science Foundation of Chinese People's Armed Police Force (Nos. WKH2006-5 and WKH2008ZO4), China 1997; Hardouin et al, 1997;Guimaraes et al, 1998;Snyder et al, 1998;Xiao et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In diseases such as congestive heart failure (CHF), chronic activation of cardiac ␤ -ARs by endogenous agonists like adrenaline and noradrenaline results in a diminished number of cardiac myocytes, which is a leading cause of morbidity and mortality [16,17] . Our data demonstrated that as the concentrations of isoprenaline increased the death rates of ventricular myocytes in vitro rose too.…”
Section: Discussionmentioning
confidence: 99%